Piwi-Interacting RNAs: A New Class of Regulator in Human Breast Cancer - Qian, Lu; Xie, Heying; Zhang, Libo; Zhao, Qian; Lü, Jinhui; Yu, Zuoren (Frontiers in Oncology, 2021)
P-element-induced wimpy testis (Piwi)-interacting RNAs (piRNAs) are a class of germline-enriched small non-coding RNA that associate with Piwi family proteins and mostly induce transposon silencing and epigenetic regulation. Emerging evidence indicated the aberrant expression of Piwil proteins and associated piRNAs in multiple types of human cancer including breast cancer. Although the majority of piRNAs in breast cancer remains unclear of the function mainly due to the variety of regulatory mechanisms, the potential of piRNAs serving as biomarkers for cancer diagnosis and prognosis or therapeutic targets for cancer treatment has been demonstrated by in vitro and in vivo studies. Herein we summarized the research progress of oncogenic or tumor suppressing piRNAs and their regulatory mechanisms in regulating human breast cancer, including piR-021285, piR-823, piR-932, piR-36712, piR-016658, piR-016975 and piR-4987. The challenges and perspectives of piRNAs in the field of human cancer were discussed.